PENGARUH LATIHAN MODIFIKASI GAWANG MENGGUNAKAN PYONGYO TERHADAP KECEPATAN TENDANGAN DOLLYO CHAGI PADA ATLET DOJANG - Della Destin Wathonilla; Elya Wibawa BS; Intan Kusuma Wardani (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study was to determine whether there is an effect of goal modification training using pyongyo on the kick speed of dollyo chagi in the dojang athletes of SMAN 1 Gerung. In this study, the methods used to obtain data were the observation method, the documentation method, and the action test method. The research design used in this study used a one group pre-test post-test design. The population is the dojang athletes of SMAN 1 Gerung. The sampling technique in this study using purposive sampling technique, the sample in this study were 10 junior athletes aged 15-17 years. The instrument in the implementation of this research is the kick speed ability test. The data analysis method used statistical analysis using the t-test formula as a test of the research hypothesis. Based on the results of data analysis, the t-count value is = 5.417. Then looking at the t-table value with a significant level of 5% at the N-1 degrees of freedom (10-1 = 9), the value = 1.833. Based on the results of the t-count value test with t-table, it is known that the t-count value is greater than the t-table value, namely = 5.417> 1.833. It means that the null hypothesis (H0) is